Hubungan antara Kepemimpinan Rendah Hati dengan Organizational Citizenship Behavior (OCB) pada Polisi di Kepolisian Daerah Sumatera Utara (Polda Sumut) - Yustinus Saragih; Rianda Elvinawaty; Naila Alfina Rizki; Mei Treisyah Zeni (Jurnal Ragam Pengabdian, 2026)
This study aims to determine the relationship between humble leadership and Organizational Citizenship Behavior (OCB) among police officers in the North Sumatra Regional Police (Polda Sumut). The results show that subordinates who perceive their leaders as having humble leadership, such as appreciation, empowerment, and the ability of superiors to value the contributions of members, tend to exhibit high levels of OCB. This means that the higher the perception of police officers regarding the humble leadership of their superiors, the higher the voluntary work behavior (OCB) exhibited by police officers. This study used a quantitative approach with analysis results showing a Pearson correlation value of 0.594 and significance of 0.000 (p < 0.05), indicating a significant relationship between humble leadership and OCB. The coefficient of determination shows that humble leadership contributes 35.3% to the formation of OCB.